2021
DOI: 10.3390/cells10123382
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of 25-Hydroxyvitamin D3 versus 1α 25-Dihydroxyvitamin D3 on Adipose Tissue Browning in CKD-Associated Cachexia

Abstract: Patients with chronic kidney disease (CKD) often have low serum concentrations of 25(OH)D3 and 1,25(OH)2D3. We investigated the differential effects of 25(OH)D3 versus 1,25(OH)2D3 repletion in mice with surgically induced CKD. Intraperitoneal supplementation of 25(OH)D3 (75 μg/kg/day) or 1,25(OH)2D3 (60 ng/kg/day) for 6 weeks normalized serum 25(OH)D3 or 1,25(OH)2D3 concentrations in CKD mice, respectively. Repletion of 25(OH)D3 normalized appetite, significantly improved weight gain, increased fat and lean ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Vitamin D promotes myogenesis and improves muscle contractility by activating the calcium-binding protein (calbindin-D9K), MAP kinase (MAPK), and phospholipase C (PLC) signaling cascade, which promote calcium influx into myocytes. Additionally, vitamin D improves energy homeostasis, reduces inflammation and intramuscular fatty infiltration, and increases muscle mass volume by reversing adipose browning [32]. Subjects with hypovitaminosis D often have difficulties in maintaining gait balance, leading to a higher chance of falls and associated injuries [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D promotes myogenesis and improves muscle contractility by activating the calcium-binding protein (calbindin-D9K), MAP kinase (MAPK), and phospholipase C (PLC) signaling cascade, which promote calcium influx into myocytes. Additionally, vitamin D improves energy homeostasis, reduces inflammation and intramuscular fatty infiltration, and increases muscle mass volume by reversing adipose browning [32]. Subjects with hypovitaminosis D often have difficulties in maintaining gait balance, leading to a higher chance of falls and associated injuries [33].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with hypovitaminosis D often have difficulties in maintaining gait balance, leading to a higher chance of falls and associated injuries [33]. Multiple studies in animal models have demonstrated the effects of exogenous vitamin D therapy in attenuating protein energy wasting and improving muscle mass and function [32]. Observational studies have also shown that HD patients with vitamin D supplementation have better nutrition, less inflammation, and a lower fracture rate [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Further, there is evolving evidence to suggest that specific biomarkers like leptin, 25 hydroxyvitamin D levels, and interleukin -1 play a specific role in CKD-related cachexia. [ 12 13 14 ] In pursuit of developing an inclusive criterion reflective of the complex interplay of nutrition and inflammation, the PEW criterion was proposed for adults. Thereafter, the criterion was adapted for use in children with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, proteomic analyses revealed the upregulation of VDBP in biological fluids from patients or animal models affected by pathologies susceptible to progressive muscle wasting or cachexia, including several types of cancer [7][8][9][10][11][12] , chronic kidney disease 13 , diabetes mellitus 14 , multiple sclerosis 15 , Parkinson's disease 16 , and COPD 17 , suggesting a potential role for VDBP in skeletal muscle homeostasis. We specifically hypothesized that VDBP could induce muscle atrophy and participate in cancer-associated muscle wasting.…”
Section: Introductionmentioning
confidence: 99%